A new genus and species of cricket from the Chapada Diamantina National Park, northeastern Brazil (Grylloidea: Phalangopsidae; Luzarinae) - Souza Dias, Pedro G.B.; De Mello, Francisco De Assis Ganeo [UNESP]; Vieira, Lelisberto Baldo [UNESP] (Magnolia Press, 2016)
A new genus and species of Luzarinae cricket (Grylloidea, Phalangopsidae) is described from the Chapada Diamantina National Park, Bahia State, northeast Brazil. Sishiniheia diamantina, n. gen. n. sp. is described based in characters of external morphology and male genitalia and is characterized by the reduced FWs, absence of stridulatory file, thick longitudinal venation and the thin, pointed and curved pseudepiphallic arms.
Keywords: Cricket; New Species; Semi-Deciduus Forest; Taxonomy